Fostering intersubjectivity and empathetic engagements in short-term education abroad: Reflections on decolonizing transnational education arrangements - Brondo, Keri; Suzanne Kent (Frontiers: The Interdisciplinary Journal of Study Abroad, 2026)
This article interrogates the assumed benefits of short-term education abroad programming within the context of colonial frameworks and neoliberal sensibilities. Reflecting on transnational programs we have run, and especially one in the Honduran Bay Islands, we apply Adkins and Messerly’s (2019) framework to decolonize education abroad to consider interventions that foster intersubjectivity and empathetic engagement. By decentering the student-as-tourist, ahistorical trend of education abroad to instead privilege local people in design and implementation, programs can be positive for both students and the communities that host them. Abstract in Spanish Este artículo cuestiona los presuntos beneficios de los programas de educación en el extranjero de corto plazo dentro del contexto de los marcos coloniales y las sensibilidades neoliberales. Con una reflexión sobre los programas transnacionales que hemos dirigido, y especialmente uno de las Islas de la Bahía de Honduras, aplicamos las ideas de Adkins y Messerly (2019) para descolonizar la educación en el extranjero con el fin de considerar intervenciones que fomenten la intersubjetividad y el compromiso empático. Al descentrar la tendencia ahistórica del “estudiante-como-turista” en la educación en el extranjero para, en su lugar, priorizar a la población local en el diseño y la implementación, los programas pueden resultar beneficiosos tanto para los estudiantes como para las comunidades que los reciben.